Pencegahan Kejadian Stunting Dengan Pola Makan Remaja Sehat: Prevention of Stunting Incidents with a Healthy Adolescent Diet - Wiyanti, Sri; Nazarena, Yunita (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Efforts to prevent stunting can start from adolescence. Young women can begin to be given knowledge and understanding about the importance of fulfilling nutrition during adolescence. Fulfilling nutrition during adolescence can prevent malnutrition during pregnancy. Adequate nutrition during pregnancy can prevent stunted growth in the fetus being conceived. The general goal is to increase the knowledge and attitude of young women towards stunting prevention through training and improving their diets. The particular goal is to increase the knowledge and attitude of young women in choosing the type of food in an effort to improve the diet of adolescents from an early age. The research method uses a descriptive design. Maternal nutrition management can start from adolescence because a mothers health status is related to her nutritional status in adolescence. So that increasing the understanding and behavior of adolescent girls regarding balanced nutrition can optimize the reduction of stunting cases. The results obtained are as follows: good knowledge increased to 60%, attitude in the good category 53.7%, after training and education. Training on improving the diet of adolescent girls is very important to increase the knowledge and attitude of adolescent girls in an effort to prevent stunting incidents in the work area of the Sebalas Ilir Palembang Health Center.